Design of Information Systems and Electrical Supplies Sales at UD Novanel Setia - Prianthoko, Mochammad Hary; Tjandrarini, A. B.; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Abstract: UD Novanel Setia is one of the trading business (UD) which is engaged in the electric equipment sale. UD Novanel Setia provide good service to meet the consumer needs with cheap and good quality electrical products that appropriate to the consumer. UD Novanel Setia have problems in the sales process. The company do not have the fact and accurate data to record an inventory process about the amount of supply goods into and out at the moment. In addition, UD Novanel Setia don’t have their sales income calculation every day, so it can’t give sale reports and information, because the data still can’t meet the needs of report creation. Based on these problems, the sales system will built on UD Novanel Setia. The system can save the sales transaction data and customer returns and also can produce information and reports related to the sale. So the owner is able to monitor the progress of the products sales in detail. The results of the study provide information to the owner about the sales development. The Information includes information entry per customer, per period income statement, statement-selling item, returned item report, inventory report and minimum inventory report. The system can calculate revenue each day and month in sales calculation process. Keywords: Information System, Sales, Sales Information System.